2001
DOI: 10.1002/bem.77.abs
|View full text |Cite
|
Sign up to set email alerts
|

Frequency response of alternating currents through the Staphylococcus aureus α‐hemolysin ion channel

Abstract: Alternating currents were measured through transmembrane ion channels formed by Staphylococcus aureus alpha-hemolysin proteins in planar bilayer membranes as part of an investigation to determine the channel's frequency response and the appropriateness of an equivalent circuit commonly used to model electrical interactions at the surface of cells. The experimental approach includes a novel method for separating the alternating current through one or more channels, which is conductive in nature, from the capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The presence of a large barrier is also inferred from the exponential form of current-voltage curves (Fig. 7), which differ from the near-linear current-voltage characteristics of water-filled, low-barrier aHL pores reconstituted in membranes (80). The combination of precise experimental results for the membrane thickness and specific capacitance is in quantitative accordance with a model in which Ab 1-42 -oligomers insert into the bilayer membrane, where they lead to domain formation.…”
Section: Discussionmentioning
confidence: 94%
“…The presence of a large barrier is also inferred from the exponential form of current-voltage curves (Fig. 7), which differ from the near-linear current-voltage characteristics of water-filled, low-barrier aHL pores reconstituted in membranes (80). The combination of precise experimental results for the membrane thickness and specific capacitance is in quantitative accordance with a model in which Ab 1-42 -oligomers insert into the bilayer membrane, where they lead to domain formation.…”
Section: Discussionmentioning
confidence: 94%
“…11 Other groups have inserted a single frequency into the voltage clamp protocol of different channel types and showed that the observed frequency response agreed with the expected response for some frequencies but not others. 12,13 Millonas and Hanck suggested the reason some frequencies did not produce the expected response is the presence of multiple rate constants in the Markov model. 12 Studies such as these, as well as others, have demonstrated that there are instances when ionic currents measured from ion channels while using impedance spectroscopy do not agree with the theoretical frequency response.…”
Section: Discussionmentioning
confidence: 99%